FLOATS LIKE A BUTTERFLY: THE RUMBLE IN THE JUNGLE AND THE ART OF COOL - Sudipto Sanyal (Celt: A Journal of Culture, English Language Teaching & Literature, 2009)
This paper discusses the Rumble in the Jungle, as the 1974 boxing world heavyweight championship bout between Muhammad Ali and George Foreman in Kinshasa, Zaire is known in popular culture, in the light of Robert Farris Thompson's analysis of the aesthetic of the cool in African tribal culture/so It connects various notions of cool to the creation of the spectacle of Ali in the documentary film on the event, When We Were Kings, and proposes a reading of Ali as a sort of culmination o/the idea of American cool.